The Toolbox for Untangling Chromosome Architecture in Immune Cells - Liu, Shuai; Zhao, Keji (Frontiers in Immunology, 2021)
The code of life is not only encrypted in the sequence of DNA, but also the way it is organized into chromosomes. Chromosome architecture is gradually recognized as an important player in regulating cell activities (e.g., controlling spatiotemporal gene expression). In the past decade, the toolbox for elucidating genome structure has been expanding, providing an opportunity to explore this under charted territory. In this review, we will introduce the recent advances of approaches for mapping spatial organization of the genome, emphasizing on applying these techniques to immune cells, and try to bridge the chromosome structure with immune cell activities.